Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! Let's begin by expressing the roots of the quadratic equation and see how we can establish the given relationship between the coefficients.
### Step-by-Step Solution
Given the quadratic equation:
[tex]\[ ax^2 + bx + c = a \][/tex]
Suppose the roots of this equation are [tex]\( r \)[/tex] and [tex]\( 4r \)[/tex]. By Vieta's formulas, the sum and product of the roots of the quadratic equation [tex]\( ax^2 + bx + c = a \)[/tex] help us establish relationships between [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex].
1. Sum of the roots:
[tex]\[ r + 4r = 5r \][/tex]
According to Vieta's formulas:
[tex]\[ \frac{-b}{a} = r + 4r \][/tex]
[tex]\[ \frac{-b}{a} = 5r \][/tex]
[tex]\[ b = -5ar \][/tex]
2. Product of the roots:
[tex]\[ r \times 4r = 4r^2 \][/tex]
According to Vieta's formulas:
[tex]\[ \frac{c}{a} = 4r^2 \][/tex]
[tex]\[ c = 4ar^2 \][/tex]
Now, the equation given in the problem is:
[tex]\[ 4b^2 = 25ac \][/tex]
Let's substitute the expressions we have for [tex]\( b \)[/tex] and [tex]\( c \)[/tex]:
3. Substitute [tex]\( b = -5ar \)[/tex]:
[tex]\[ 4b^2 = 4(-5ar)^2 \][/tex]
[tex]\[ 4b^2 = 4 \times 25a^2r^2 \][/tex]
[tex]\[ 4b^2 = 100a^2r^2 \][/tex]
4. Now, substitute [tex]\( c = 4ar^2 \)[/tex]:
[tex]\[ 25ac = 25a \times 4ar^2 \][/tex]
[tex]\[ 25ac = 25 \times 4a^2r^2 \][/tex]
[tex]\[ 25ac = 100a^2r^2 \][/tex]
We see that:
[tex]\[ 4b^2 = 100a^2r^2 \][/tex]
[tex]\[ 25ac = 100a^2r^2 \][/tex]
Since both expressions are equal, we have:
[tex]\[ 4b^2 = 25ac \][/tex]
Therefore, we have successfully demonstrated that [tex]\( 4b^2 = 25ac \)[/tex] when one root of the equation [tex]\( ax^2 + bx + c = a \)[/tex] is four times the other root.
### Step-by-Step Solution
Given the quadratic equation:
[tex]\[ ax^2 + bx + c = a \][/tex]
Suppose the roots of this equation are [tex]\( r \)[/tex] and [tex]\( 4r \)[/tex]. By Vieta's formulas, the sum and product of the roots of the quadratic equation [tex]\( ax^2 + bx + c = a \)[/tex] help us establish relationships between [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex].
1. Sum of the roots:
[tex]\[ r + 4r = 5r \][/tex]
According to Vieta's formulas:
[tex]\[ \frac{-b}{a} = r + 4r \][/tex]
[tex]\[ \frac{-b}{a} = 5r \][/tex]
[tex]\[ b = -5ar \][/tex]
2. Product of the roots:
[tex]\[ r \times 4r = 4r^2 \][/tex]
According to Vieta's formulas:
[tex]\[ \frac{c}{a} = 4r^2 \][/tex]
[tex]\[ c = 4ar^2 \][/tex]
Now, the equation given in the problem is:
[tex]\[ 4b^2 = 25ac \][/tex]
Let's substitute the expressions we have for [tex]\( b \)[/tex] and [tex]\( c \)[/tex]:
3. Substitute [tex]\( b = -5ar \)[/tex]:
[tex]\[ 4b^2 = 4(-5ar)^2 \][/tex]
[tex]\[ 4b^2 = 4 \times 25a^2r^2 \][/tex]
[tex]\[ 4b^2 = 100a^2r^2 \][/tex]
4. Now, substitute [tex]\( c = 4ar^2 \)[/tex]:
[tex]\[ 25ac = 25a \times 4ar^2 \][/tex]
[tex]\[ 25ac = 25 \times 4a^2r^2 \][/tex]
[tex]\[ 25ac = 100a^2r^2 \][/tex]
We see that:
[tex]\[ 4b^2 = 100a^2r^2 \][/tex]
[tex]\[ 25ac = 100a^2r^2 \][/tex]
Since both expressions are equal, we have:
[tex]\[ 4b^2 = 25ac \][/tex]
Therefore, we have successfully demonstrated that [tex]\( 4b^2 = 25ac \)[/tex] when one root of the equation [tex]\( ax^2 + bx + c = a \)[/tex] is four times the other root.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.